The Unfinished Revolution : Voices from the Global Fight for Women's Rights - Worden, Minky (Book collections on Project MUSE., 2012)
The Unfinished Revolution tells the story of the global struggle to secure basic rights for women and girls, including in the Middle East where the Arab Spring raised high hopes, but the political revolutions are so far insufficient to guarantee progress. Around the world, women and girls are trafficked into forced labor and sex slavery, trapped in conflict zones where rape is a weapon of war, prevented from attending school, and kept from making deeply personal choices in their private lives, such as whom and when to marry. In many countries, women are second-class citizens by law. In others, religion and traditions block freedoms such as the right to work, study or access health care. Even in the United States, women who are victims of sexual violence often do not see their attackers brought to justice.